2016
DOI: 10.1111/xen.12239
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody reactivity against xenogeneic N‐glycolylneuraminic acid and galactose‐α‐1,3‐galactose antigen

Abstract: We showed that IgG-mediated CDC was detected in Neu5Gc-overexpressed HEK293 cells incubated with human sera; however, this antibody reactivity to Neu5Gc was highly variable among individuals. Our results suggest that additional modifications to the CMAH gene should be considered for widespread use of pig organs for human transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…In addition, a study of a Korean population demonstrated that IgM andIgG antibodies against Neu5Gc were not significantly different among subjects of various blood groups and age [32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study of a Korean population demonstrated that IgM andIgG antibodies against Neu5Gc were not significantly different among subjects of various blood groups and age [32]. …”
Section: Discussionmentioning
confidence: 99%
“…The Neu5Gc-PAA conjugate which was used for ELISA in the present study does not present a sufficiently diverse range of antigens to accurately measure the amount of anti-Neu5Gc in the serum, and therefore does not give a complete comparison of the antibody levels in humans. In future experiments, it will be necessary to use more pertinent methodologies for measuring anti-Neu5Gc antibodies [30, 32, 35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…The complement-mediated early rejection is mainly caused by preformed antibodies directed against galactose-α1,3-galactose-β1,4-N-acetylglucosamine-R epitope (αGal) 1,2 and other non-Gal carbohydrate epitopes such as Neu5Gc [3][4][5] or the glycan produced by porcine β1,4-N-acetyl-galactosaminyltransferase 2 (B4GALNT2) 6 on porcine cells, which in turn rapidly destroys the porcine graft. The development of pigs deficient in αGal (GGTA1-Ko) and Neu5Gc (CMAH-Ko) 7,8 and the transgenic expression of human complement regulatory proteins [9][10][11][12][13][14] helped to overcome these barriers and shifted the research focus to the following cellular and late rejection processes against porcine tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Acute vascular rejection occurs within a few days or weeks and is characterized by proinflammatory and procoagulatory activation of the vascular endothelium, complement activation, thrombotic microangiopathy and infiltration of innate immune cells into the graft . This response is also initiated by preformed antibodies, with evidence indicating a role for non‐Gal porcine antigens including N‐glycolylneuraminic acid (Neu5Gc), synthesized by cytidine monophospho‐N‐acetylneuraminic acid hydroxylase ( CMAH ), and surface glycans including the Sd(a) blood group antigen produced by β‐1,4‐N‐acetyl‐galactosaminyl transferase 2 ( B4GALNT2 ) …”
Section: Introductionmentioning
confidence: 99%